The Strength of Two Indicators of Social Position on Oral Health Among Persons Over the Age of 80 Years - Kirsten Avlund, PhD, DMedSci; Poul Holm-Pedersen, DDS, Dr. Odont; Douglas E. Morse, DDS, (Blackwell Synergy, 2005)
The objective of the present study is to analyze how two dimensions of social position, education and social class, are associated with oral health among generally healthy, community-dwelling persons over the age of 80 years.